Pelatihan Penerapan Model Membelajaran 4-Step-Jigsaw Untuk Meningkatkan Profesionalisme Guru Kimia - Effendi Hasibuan, Muhammad Haris; Haryanto, Haryanto; Sadikin , Ali (Jurnal JUPEMA, 2025)
Indonesian government has recommended chemistry teachers to implement active learning models such as Jigsaw when teaching. Jigsaw learning model provides many benefits for students including the improvement of learning outcomes and the reduction of anxiety in learning science. However, the facts in the field show that the adoption of the Jigsaw learning is still minimal. Two constraints are the lack of knowledge and skills of chemistry teachers in using the learning model and the absence of training. Therefore, a training is needed to help chemistry teachers to be able to apply the Jigsaw learning model. The training has been carried out at SMAN 2 Muaro Jambi in 4 stages. Stage I is face-to-face lectures, stage II involves teaching practice, stage III is mentoring for the revision of the Learning Plan (RPP) based on the jigsaw model, and stage IV is evaluation. The evaluation results show that this training has been successful in improving teachers' knowledge and skills in applying the jigsaw model. Teachers are expected to continue using the jigsaw learning model when teaching chemistry. Abstrak. Pemerintah Indonesia telah merekomendasikan agar guru-guru kimia menerapkan model-model pembelajaran aktif seperti Jigsaw saat mengajar. Model pembelajaran jigsaw banyak memberikan manfaat bagi siswa meliputi peningkatan hasil belajar bahkan membantu siswa menurunkan kecemasan dalam belajar sains. Namun fakta dilapangan  menunjukkan penerapan model pembelajaran Jigsaw masih minim. Dua masalah penyebabnya adalah kurangnya pengetahuan dan keterampilan guru kimia dalam menggunakan model pembelajaran tersebut serta tiadanya pelatihan. Oleh karena itu, perlu dilakukan pelatihan untuk membantu guru-guru kimia agar mampu menerapkan model pembelajaran Jigsaw. Pelatihan tersebut telah dilaksanakan di SMAN 2 Muaro Jambi dalam 4 tahap. Tahap I adalah kuliah tatap muka, tahap II melibatkan praktek mengajar, tahap III adalah mentoring untuk revisi Rencana Pelaksanaan Pembelajaran (RPP) berbasis model pembelajaran jigsaw, dan tahap IV adalah evaluasi. Hasil evaluasi menunjukkan bahwa  pelatihan ini telah berhasil meningkatkan pengetahuan dan keterampilan guru dalam menerapkan model jigsaw. Guru diharapkan akan terus menggunakan model pembelajaran jigsaw saat mengajar kimia